USE OF BUSINESS GAMES IN GEOGRAPHY LESSONS AS A MEANS OF INCREASING THE COGNITIVE STRESS OF EDUCATION - Povtorachenko Н.О. (Pedagogy of Higher and Secondary Education, 2022)
In article problems of use of business games at lessons ofgeography as way of development of cognitive interest of pupils are considered. The analysis of concepts "business game" in the psycholog-pedagogical literature is shown. Ir is sent results of questioning and testing with the purpose of definition of quality of knowledge ofpupils and deelopments of cognitive interest of pupils to geography.